Ghrelin Protects Against Insulin-Induced Hypoglycemia in a Mouse Model of Type 1 Diabetes Mellitus - Shankar, Kripa; Gupta, Deepali; Mani, Bharath K.; Findley, Brianna G.; Osborne-Lawrence, Sherri; Metzger, Nathan P.; Liu, Chen; Berglund, Eric D.; Zigman, Jeffrey M. (Frontiers in Endocrinology, 2020)
Insulin-induced hypoglycemia is a major limiting factor in maintaining optimal blood glucose in patients with type 1 diabetes and advanced type 2 diabetes. Luckily, a counterregulatory response (CRR) system exists to help minimize and reverse hypoglycemia, although more studies are needed to better characterize its components. Recently, we showed that the hormone ghrelin is permissive for the normal CRR to insulin-induced hypoglycemia when assessed in mice without diabetes. Here, we tested the hypothesis that ghrelin also is protective against insulin-induced hypoglycemia in the streptozotocin (STZ) mouse model of type 1 diabetes. STZ-treated ghrelin-knockout (KO) mice as well as STZ-treated wild-type (WT) littermates were subjected to a low-dose hyperinsulinemic-hypoglycemic clamp procedure. The STZ-treated ghrelin-KO mice required a much higher glucose infusion rate than the STZ-treated WT mice. Also, the STZ-treated ghrelin-KO mice exhibited attenuated plasma epinephrine and norepinephrine responses to the insulin-induced hypoglycemia. Taken together, our data suggest that without ghrelin, STZ-treated mice modeling type 1 diabetes are unable to mount the usual CRR to insulin-induced hypoglycemia.